Munidopsis aries - Baba, Keiji; Macpherson, Enrique; Poore, Gary C. B.; Ahyong, Shane T.; Bermudez, Adriana; Cabezas, Patricia; Lin, Chia-Wei; Nizinski, Martha; Rodrigues, Celso; Schnabel, Kareen E. (Zenodo, 2008)
Munidopsis aries (A. Milne Edwards, 1880) Orophorhynchus aries A. Milne Edwards, 1880: 58 (Bequia, 2912 m). — A Milne Edwards & Bouvier, 1894a: 209. — A. Milne Edwards & a: 111, pl. 9, figs 7–11, pl. 10, figs 1–2. Munidopsis aries . — Benedict, 1902: 316 (key). — Pequegnat & Pequegnat, 1970: 139 (key). — Pequegnat & Pequegnat, 1971: 5 (key), fig. 12B. — Wenner, 1982: 367 (off New England, 3605–3642 m). — Gore, 1983: 203, fig. 2 (Venezuelan Basin (Caribbean Sea, 3475–4095 m). — Macpherson & Segonzac, 2005: 15, fig. 3 (Off Mauritania, off South Africa, Iberia abyssal plain, off Angola, NW Atlantic, NE Atlantic, 2615–5320 m). — Macpherson, 2007: 39 (Réunion Island, 3180–3480 m). Munidopsis sundi Sivertsen & Holthuis, 1956: 44, pl. 4, figs 2, 4 (type locality: south of Azores, 34º 59´N, 33º 01´W, 2615 m, holotype, female, BMBN). — Pequegnat & Pequegnat, 1971: 22, fig. 13 (Caribbean Sea (Colombian Basin), 4151 m). — Wenner, 1982: 371 (Middle Atlantic Bight, 2933 m). Type data: holotype, male, MCZ 4761. Type locality: Bequia, 2912 m. : Published as part of Baba, Keiji, Macpherson, Enrique, Poore, Gary C. B., Ahyong, Shane T., Bermudez, Adriana, Cabezas, Patricia, Lin, Chia-Wei, Nizinski, Martha, Rodrigues, Celso & Schnabel, Kareen E., 2008, Catalogue of squat lobsters of the world (Crustacea: Decapoda: Anomura-families Chirostylidae, Galatheidae and Kiwaidae), pp. 1-220 in Zootaxa 1905 (1) on page 132, DOI: 10.11646/zootaxa.1905.1.1, http://zenodo.org/record/5134587 : {"references": ["Milne Edwards, A. (1880) Reports on the results of dredging under the supervision of Alexander Agassiz, in the Gulf of Mexico and in the Caribbean Sea, etc. VIII. Etudes preliminaires sur les Crustaces. Bulletin of the Museum of Comparative Zoology at Harvard College, 8, 1 - 168, pls 1, 2.", "Milne Edwards, A. & Bouvier, E. L. (1894 a) Considerations generales sur la famille des Galatheides. Annales des Sciences Naturelles, Zoologie (ser. 7), 16, 191 - 327.", "Benedict, J. E. (1902) Description of a new genus and forty six new species of crustaceans of the family Galatheidae with a list of the known marine species. Proceedings of the Biological Society of Washington, 26, 243 - 334.", "Pequegnat, L. H. & Pequegnat, W. E. (1970) Deep-sea anomurans of superfamily Galatheoidea with description of three new species. In: Pequegnat, W. E. & Chace, F. A. (eds), Contributions on the Biology of the Gulf of Mexico. Texas A & M University, pp. 125 - 170.", "Pequegnat, W. E. & Pequegnat, L. H. (1971) New species and new records of Munidopsis (Decapoda: Galatheidae) from the Gulf of Mexico and Caribbean Sea (Supplement to Texas A & M University Oceanographic Studies. Volume 1). Gulf Publishing Co, Houston, 25 pp.", "Wenner, E. L. (1982) Notes on the distribution and biology of Galatheidae and Chirostylidae (Decapoda: Anomura) from the middle Atlantic Bight. Journal of Crustacean Biology, 2, 360 - 377.", "Gore, R. H. (1983) Notes on rare species of Munidopsis (Anomura: Galatheidae) and Ethusina (Brachyura: Dorippidae) collected by the USNS Barlett in the Venezuela Basin, Caribbean Sea. Proceedings of the Academy of Natural Sciences of Philadelphia, 135, 200 - 217.", "Macpherson, E. & Segonzac, M. (2005) Species of the genus Munidopsis (Crustacea, Decapoda, Galatheidae) from the deep Atlantic Ocean, including cold-seep and hydrothermal vent areas. Zootaxa, 1095, 1 - 60.", "Macpherson, E. (2007) Species of the genus Munidopsis Whiteaves, 1784 from the Indian and Pacific Oceans and reestablishment of the genus Galacantha A. Milne-Edwards, 1880 (Crustacea, Decapoda, Galatheidae). Zootaxa, 1417, 1 - 135.", "Sivertsen, E. & Holthuis, L. B. (1956) Crustacea Decapoda (The Penaeidea and Stenopodidea excepted) Report on the Scientific Results of the \" Michael Sars \" North Atlantic Deep-Sea Expedition, 1910, 5, 1 - 54, pls 1 - 4."]}